The Significance of Taking Antiretroviral Medications for African-Born People Living with HIV and Residing in Minnesota - Alina Cernasev; William L. Larson; Cynthia Peden-McAlpine; Todd Rockwood; Paul L. Ranelli; Olihe Okoro; Jon C. Schommer (MDPI AG, 2020)
Thanks to the development of antiretroviral (ART) medications, HIV is now a chronic and manageable disease. This study aimed to (1) capture the experiences of African-born persons living with HIV and taking antiretroviral treatment, and (2) explore the impact of social and cultural factors on their decisions to follow the prescribed treatment. For this study, a qualitative approach was used. The participants were recruited via fliers, then screened for inclusion and exclusion criteria. Recruitment of the participants continued until data saturation occurred. The interview guide was developed based on the extensive literature and recommendations from the clinical team. In-person narrative interviews were conducted with 14 participants-African-born persons living with HIV and residing in Minnesota. Thematic Analysis revealed three emergent themes: "To exist I have to take the medicine"; barriers and facilitators in taking ART medications; and the power of spirituality and prayers. The findings of this study paint a picture of African-born persons living with HIV, and their experiences with ART medications. This study not only presents the participants' medication experiences and their significance, but also tells their stories of how God and prayers play a significant role in helping them to get through the difficult moments of their lives.